Leader humility and team innovation: The role of team reflexivity and team proactive personality - Leblanc, Pierre-Marc; Rousseau, Vincent; Harvey, Jean-François (Journal of Organizational Behavior, 2022)
Despite the recent surge of research on leader humility, it remains unclear how and when teams benefit from it. Drawing on social cognitive theory, we propose a moderated mediation model that we test using multisource, time-lagged data collected from 71 teams in a university-affiliated hospital. We find that humble leaders indirectly enhance team innovation via greater team reflexivity. Additionally, we consider the average level of proactive personality of team members as a boundary condition of the positive effect of leader humility. Our results show that leader humility prompts team reflexivity only when team mean level of proactive personality is high, which in turn increases team innovation. Bridging social cognitive theory with research on humble leadership in teams, our study offers important implications for both theory and practice.
Keywords: leader humility